A comprehensive review on zircon (U–Pb) geochronology, geochemistry and geological significance of granite rocks, provenance, tectonic implications, exhumation history, current status, and perspectives. Issue 9 (31st May 2022) - Nazir, Nusrat; Ayyamperumal, Ramamoorthy; Majeed, Khawaja Umair; Zhang, Chengjun
Abstract : The mineralization in this area is more closely related to the shoshonitic Niuxinshan meddling complex (NIC), which helps to depict concurrent edge magmatism metallogeny. In the present investigation, new geochronological and geochemical data are combined with previously disseminated isotopic data from granitic rocks in the NIC to establish the situation of the region's structural setting change and determine its bearing on territorial metallogeny. The new geochronological data suggest that structural change could have occurred between 155 and 185 Ma. The granitic rocks of the NIC can be geochemically divided into two groups. The geochemical signature of one group displays high rare earth element (REE) designs with irrelevant Eu anomalies, lower Yb, higher Sr, and negative Nb–Ta–Ti (NTT) abnormalities, demonstrating a volcanic‐curve climate with a thickened outside layer in a focalized setting. The other group has level REE designs with obvious regrettable Eu anomalies, higher Yb, lower Sr, and moderate NTT anomalies, indicating an intra‐plate extensional climate with a decreasing outside. According to geochronologic and isotopic data, the mineralization is Late Jurassic (155 Ma). This has been deciphered to be hereditarily associated with the crystallization of the complex's shallow crustal‐sourced bits. In addition, a structural model is presented that provides a possible explanation for the abundant polymetallic mineralization that occurs in the northern margin of the NCC after 155 Ma. Abstract : Geochemistry and geochronlogy of granite rocks.